Diversity and distribution of nirS-type denitrifiers as a biological indicator in response to environmental gradients in the eutrophied Haizhou Bay, China. Issue 1 (1st January 2019) - Wang, Chunyan; Song, Jianyang; Hu, Xiaoling; Zhang, Yumei; Wang, Hongyu; Li, Lixin
ABSTRACT: Denitrifying bacterial communities play an important role in nitrogen removal. The diversity, abundance and distribution of denitrifiers can be applied in eutrophication assessment for the bay ecosystems. In this study, the composition and variation of cytochrome cd1-type nitrite reductase gene ( nirS )-type denitrifiers in the sediments of Haizhou Bay were investigated by using a PCR-based cloning approach. A total of 156 valid sequences were grouped into 76 OTUs based on 97% sequence similarity. The nirS sequences were identified with their closest-matched sequences from sediments of estuary and eutrophied bay, indicating similarity of the denitrifying bacterial communities in similar coastal environments. Canonical correspondence analysis indicated that nitrogen nutrient and dissolved oxygen were the major contributing parameters for the diversity and spatial distribution of denitrifying bacteria of Haizhou Bay.